2015
DOI: 10.1097/qad.0000000000000698
|View full text |Cite
|
Sign up to set email alerts
|

Soluble CD40 ligand contributes to dendritic cell-mediated T-cell dysfunction in HIV-1 infection

Abstract: OBJECTIVE Plasma soluble CD40L (sCD40L) is increased during human immunodeficiency virus-1 (HIV) infection, but it is unknown whether it circulates in monomeric or multimeric forms, and whether the circulating forms have differential effects on myeloid dendritic cell (DC) function and adaptive regulation. DESIGN sCD40L forms were measured in plasma samples from HIV-infected donors. The effects of sCD40L forms on DC function were measured in vitro. METHODS To delineate which forms of sCD40L are present in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 43 publications
0
15
1
Order By: Relevance
“…We found a positive correlation between plasma sST2 levels and the Kyn/Trp ratio, which suggests that immune activation may be induced by metabolites generated either by gut microbes and/or by IFNγ following systemic viral infection [ 52 , 53 ]. We have previously shown that IDO activity is mediated by sCD40L [ 54 ], another marker of immune activation expressed by activated T cells [ 55 ] and a strong inducer of B cells and antigen presenting cells [ 56 ]. Among different markers of inflammation assessed herein, we observed a strong correlation of sST2 levels with sCD40L in EHI.…”
Section: Discussionmentioning
confidence: 99%
“…We found a positive correlation between plasma sST2 levels and the Kyn/Trp ratio, which suggests that immune activation may be induced by metabolites generated either by gut microbes and/or by IFNγ following systemic viral infection [ 52 , 53 ]. We have previously shown that IDO activity is mediated by sCD40L [ 54 ], another marker of immune activation expressed by activated T cells [ 55 ] and a strong inducer of B cells and antigen presenting cells [ 56 ]. Among different markers of inflammation assessed herein, we observed a strong correlation of sST2 levels with sCD40L in EHI.…”
Section: Discussionmentioning
confidence: 99%
“…If we consider these results and the crucial role of sCD40L in cancer microenvironment, this biomarker could be useful in a stromal tumor such as PDAC, not forgetting that CA19.9 is negative in ~20% of PDAC patients, 24 as found in six of our patients.…”
Section: Discussionmentioning
confidence: 66%
“…In vitro and in vivo studies display a crucial involvement of the CD40 pathway in regulating the immune reaction and fibrosis in PDAC, a tumor with a strong interaction between cancer cells and microenvironment. 24 The clinical significance of serum sCD40L as a potential diagnostic and prognostic biomarker in patients with PDAC has been recently reported. 17 Chung and Lim demonstrated that the serum sCD40L levels were significantly increased in the PDAC group compared with the healthy and chronic pancreatitis groups.…”
Section: Discussionmentioning
confidence: 99%
“…Despite being infected and contrary to C, HIV + -P had sCD40L levels comparable to HD. Others have reported that sCD40L may impair dendritic cell functionality during HIV infection ( Miller et al, 2015 ). Thus, our result would indicate that HIV + -P would be protected from this phenomenon.…”
Section: Discussionmentioning
confidence: 99%